Effects of some alkaloids on the dark-sided cutworm Euxoa messoria (Lepidoptera: Noctuidae). - Devitt, Brenda D. (University of Ottawa (Canada), 1978)
The dark-sided cutworm, Euxoa messoria (Harr.) was reared under laboratory conditions on 8 artificial diets, a meridic diet containing various concentrations of one of the alkaloids, veratrine, berberine, nicotine, or atropine, and on two varieties of Nicotiana tabacum, Lonibow and Delhi-34. Observations of the development times, larval and pupal weights, survival, and number and widths of head capsules were recorded. Feeding preference studies were carried out to look at possible food choice mechanisms used by the larvae. Larvae showed quantitative requirements for ascorbic acid and cholesterol. Soybean protein was unsuitable as the sole protein source but it did supplement casein. Wheat germ provided an unknown nutritional quality to the diet which improved developmental characteristics. Chronic exposure to alkaloid diets demonstrated that survival and developmental characteristics are variously affected by the source and concentration of alkaloid. Larvae demonstrated a tolerance to levels of 0.01%, 0.03%, and 0.1%, berberine; 0.01%, and 0.03% nicotine; and 0.01%, 0.03% and 0.1% atropine. Atropine at all levels tested enhanced survival and larval size. Detrimental effects on growth, development rates survival and/or number of instars were observed in larvae fed dietary levels of 0.3% and 1.0% berberine; 0.1%, 0.3%, and 1.0% nicotine; 0.3% and 1.0% atropine; and 0.01%, 0.03%, 0.1%, and 0.3%, and 1.0% veratrine, indicating that this insect is susceptible to these compounds at these levels. Larvae were most sensitive to the detrimental (or antibiosis) effects of the alkaloids berberine and nicotine in the early stages of development. There was a degree of plasticity observed in the duration of the prepupal period which Allowed the development rates of individuals fed various levels of an alkaloid to become synchronized, thus ensuring that the adults emerged at roughly the same time. The developmental characteristics of larvae fed two varieties of N. tabacum, Lonibow and Delhi-34, indicated that Delhi-34 shows some resistance to the larvae by decreasing survival, larval and pupal sizes, and increasing the development times. E. messoria demonstrates a definite preference for some food sources over others, and responds to both nutritive and secondary plant compounds in making a choice. Sucrose, nicotine, and atropine are phagostimulants to the larvae while berberine (at 0.03%, 0.1%, 0.3%, and 1.0%) and veratrine (at all levels tested) are feeding deterrents. The threshold level for the antifeedant effect of berberine appears to be 0.01%. Response to the alkaloids seems to be dependant upon the presence of nutrient compounds. Sucrose mixed with atropine had a synergistic effect on the feeding response. Larvae show a preference for some varieties and species of Nicotiana, and strongly preferred Atropa belladona over tobacco. Both the antennae and maxillary palps are involved in host selection. Responses by maxillectomized larvae suggest that sucrose receptors are located on the maxillary palps and in the buccal cavity, and that the receptors responsible for the synergistic effect of sucrose and atropine are also on the maxillary palps. The presence of the maxillary palps appears to be essential for feeding to occur. Larval preference for a food source does not guarantee the choice of a diet which is suitable for normal growth and development.
Keywords: Biology, Entomology.